Health Education on Nutrition Management Reduces Blood Sugar Levels in Diabetes Mellitus Clients - Widara, Jihan Zinnia; Sukesih, Sukesih; Jauhar, Muhamad (CV Media Inti Teknologi, 2024)
This study aimed to Analyze the influence and health support for the nutritional management of blood sugar levels in diabetes mellitus clients in the working area of the Gribig Community Health Center, Kudus Regency. The research design uses a quasi-experiment with a Pretest and a Post-test with a control group design. This research was conducted from June to July 2024 in the working area of the Gribig Community Health Center, Kudus Regency. Using purposive sampling techniques, the total sample was 26 respondents for each intervention and control group. The inclusion criteria for clients with diabetes mellitus are having a current blood sugar level of ≥150 mg/dL. The intervention was to provide health education on nutrition management for 45 minutes using a nutrition management workbook and monitor nutritional patterns for 7 days. The instrument uses an Autocheck CE – 0197 brand glucometer, observation sheet, and nutrition management book. Data analysis uses paired sample tests and independent tests. Research results showed there is a statistically significant effect of nutritional management health education on blood sugar levels in diabetes mellitus clients in the working area of the Gribig Community Health Center, Kudus Regency, with p-value 0,028 (p<0,05). So, it can be concluded that health education on nutritional management can control blood sugar levels in clients with diabetes mellitus. This educational model and media can be applied and become an innovative health program in health service facilities in nutrition management in the community.